Resource Use and Costs up to Two Years Post Diagnosis Among Newly Diagnosed COPD Patients in the UK Primary Care Setting: A Retrospective Cohort Study. (4th May 2015) - Punekar, Yogesh Suresh; Wurst, Keele; Shukla, Amit
Abstract: The objective of this study was to estimate the annual resource use and costs before and after COPD diagnosis and compare it across stages of airflow obstruction and levels of dyspnoea in the UK primary care setting. A retrospective cohort of newly diagnosed COPD patients (1/1/2008-31/12/2009) was identified in the UK Clinical Practice Research Datalink (CPRD). Resource use did not include medication costs and comprised of exacerbations, all cause GP interactions, and non-COPD hospitalisations, which were estimated for up to 12 months before and 24 months after COPD diagnosis. It was further stratified using baseline characteristics, Medical Research Council (MRC) dyspnoea score, and stages of airflow limitation. COPD costs were estimated using NHS reference costs. The analysis included 7881 newly diagnosed COPD patients (mean age, 67.2 years; 45% females). In the 2 years follow-up, the cohort experienced moderate and severe exacerbations, non-COPD hospitalisations, and GP surgery visits at an annual rate of 0.51, 0.13, 0.47, and 12.85, respectively. All resource components showed an upward trend with increase airflow limitation and dyspnoea. GP interactions accounted for 58.5% of annual per patient COPD management costs, estimated to be £2047 during the observation period. The annual costs doubled from patients with low levels of dyspnoea (MRC = 1; £1473) to those with high levels of dyspnoea (MRC = 5; £3243). COPD management costs in the primary care setting continued to remain high up to 2 years following initial diagnosis. The cost burden increased with high levels of dyspnoea and airflow obstruction, suggesting that both measures can identify patients requiring increased monitoring.